Comunicação entre mãe-filho em alojamento conjunto à luz dos fatores proxêmicos - Vasconcelos, Simone Gonçalves (2006)
Proxemics is a neologism which designates the set of observations and theories relating to the use man makes of his space, comprising a form of non-verbal communication. Proxemic communication studies the social meaning of space, that is, it studies how man unconsciously structures his own space. In this research, proxemic communication between mother and child in shared accommodation is approached. A comparative judgment is made between binomes with negative and positive blood test results for HIV, the general objective being analysis of mother-child interactions during diaper-changing of babies in shared accommodation, in the light of proxemic factors. A descriptive and quantitative exploratory study was undertaken, between December 2005 and February 2006, in a shared accommodation unit of a public maternity hospital in Fortaleza, Ceará, Brazil, using video footage to evaluate communication. Filming was performed in shared accommodation rooms, during the first 48 hours of life of neonates, in which anthropometrics, diaper-changing, bathing and vaccination of newborns take place. The population comprised a convenient sample of a binome group (G1; n=5), in which the mother does not test positively for HIV and a second group (G2, n=3) in which the mother was aware of positive blood test result for HIV, prior to childbirth. Footage filmed at time of diaper changes was analyzed by judges, in compliance with the theoretical benchmark of Hall (1986) regarding proxemic communication and scenes were finalized when repetition of proxemic communication components was observed. For analysis, a previously-prepared script was used, noting proxemic factors: tone of voice, distance, contact behavior and visual contact. According to the data, a statistical difference was generated for visual code and tone of voice factors. There was absolute concordance amongst judges for the posture factor. Nevertheless, relative data (%) permit inference of certain assumptions, notably: the “diaper-change” situation was not the moment in which mothers demonstrated affection for their children; the presence of a high number of interactions on a lateral axis; gaze directed to interlocutor maintained a margin close to averted; most interactions found with sociopetal axis may reflect need for mother to remain close to child for the change and the need for silence during procedure. Studies may be undertaken with a view to expanding the process of evaluation of communication in initial phases of life, as knowledge of the communicative process between mother and child may assist in judgment of validity of implementation of efforts to make it as healthy as possible from the first hours postpartum, especially as patients with HIV/AIDS have a particular life story, marked by painful episodes in view of the disease’s symptoms and the uncertainty regarding prognosis.